Kajian Waktu Irigasi pada Tanaman Selada (Lactuva Sativa) Organik Untuk Budidaya Tanaman dengan Naungan dan Tanpa Naungan di Yayasan Bina Sarana Bakti Cisarua Bogor - Desi Novalia; Muhammad Idrus; I gde Darmaputra (Jurusan Teknologi Pertanian, 2020)
The Bina Sarana Bakti Foundation (YBSB) implements an organic farming system, which is an agricultural management system with a terrace design with permanent beds that can ecologically (environmentally) improve land quality, provide stable and sustainable yields and income into the future. To provide water for plants so that organic farming can take place throughout the season, both in the rainy season and in the dry season, water reservoirs are built using existing water sources. Utilization of water in the cultivation of organic lettuce at the Bina Sarana Bakti Foundation is carried out with 2-level irrigation hose treatment, namely the interval of providing irrigation water for 3 days and 4 days. Data analysis used t test at 5% real level. The results showed that the theoretical amount of water for lettuce at the Bina Sarana Bakti Foundation was 714 l/bed/season which was almost the same as the actual water use of lettuce with an interval of 3 days of irrigation water including additional liquid fertilizer from rabbit urine. + water in open land in shade is 720 l/bed/season, however, it is much lower than the interval of providing irrigation water for 4 days in open land without shade, namely 4,980 l/bed/season. The production of lettuce in shade with an interval of 3 days of 30.4 kg/bed/season was much greater than the production of lettuce without shade with an interval of 4 days of irrigation water, which was only 24.7 kg/bed/season. The productivity of irrigation water for shaded lettuce with the provision of irrigation water at an interval of 3 days of irrigation is 42.22 kg/m³, much higher and more effective than lettuce without shade with an interval of 4 days of irrigation which is only 4.96 kg/m³. Keywords: irrigation time interval, lettuce plants, no shade, shade, and water productivity.